Measuring service quality in Samarahan District Office / Khatijah Reduan, Laura Peritha Tupi & Faizah Mazlan Tajuddin - Reduan, Khatijah; Tupi, Laura Peritha; Mazlan Tajuddin, Faizah (2011)
The services provides by Samarahan District Office (SDO) is a type of public services that are important for their local people in order to give advantages and administrating their local people needs. The project paper covers the measurement of the quality of services provided by SDO’s services. These SDO service quality related to the characteristic by namely, organisation, product or services is judge by the clients. The good quality services provided by SDO can only be achieved with the existence of excellent staffs in different level or fields from aspect of knowledgeable, expert in work, discipline and committed in their work and productive. The purposed of the research is about the service quality in SDO by measuring the quality level of service provided by the staffs to the SDO’s customers. The project paper also simply identified the level of achievement of the SDO services towards their customer in a standard of the quality service. The level or timeline use by the SDO itself in delivering their services is difference and based on their customer charter. This project paper makes studies on their service quality from both internal and external customer of SDO in order to gained the result of the services either good service quality or not. The questionnaire and the customer feedback or opinion have facilitated and determined such benefit and problem occurred in the SDO movement to achieve ‘he service quality. Therefore, the respondent either internal or external staffs and client charter been used as a guideline to guided in measuring the service quality for SDO. All in this study used a research methodology such as questionnaire which has been distributed to all the respondents. The feedback from the respondent is used for the study’s finding and determined the level of quality services in SDO and there are several finding showed that there are need some improvement on the SDO services. Therefore, there are also showed that the previous studied supports that the public sector or service need to improve their services to meet the qua ity standard. The studies have helps the public service especially in SDO with some ideas and opinion to help them generates ideas to improve or develop good services in the future or present to make the public in their responsible areas felt satisfied and meet the quality standard as other agencies or government departments.